Reason and Narration with Ibn Rushd (Averroes) - Khattab, Mohammad Ali (Advances in Social Sciences Research Journal, 2019)
Ibn Rushd was distinguished by his bewildering personality, stemming from being a jurist and theologist, a philosopher and physician, and an astronomer. When researching his writings, we found that he encourages a lot of reason, and puts aside everything related to revelation, at other times, you find him defending Revelation and does not care about the mind, and you see him attacking the Asha’ries. In some cases, he defends them in other places, and in some cases, he adopts the views of the predecessor, making him a collector of all contradictions. However, the beholder in his biography and history knows that he went through several stages, stamped with jurisprudential stability, moderation in judging the opponents, and a victory for the doctrine of Tafweedh.